The students preparedness for Merapi eruption: Case of SMP Negeri 2 Pakem - Wismoko Putri, Raudya Setya; Setiawati, Winda (Universitas Negeri Yogyakarta, 2024)
This study aims to find out: (1) the level of preparedness of students of SMP Negeri 2 Pakem students to face the Merapi eruption disaster, (2) the efforts made by the school to improve their preparedness to face the Merapi eruption disaster, and (3) the school's constraints in improving their preparedness. This study used mixed methods. The research model was a sequential exploratory design. The data were collected through questionnaires, interviews, and documentation. The qualitative data trustworthiness was enhanced by source triangulation involving 3 sources, namely the Principal, Social Studies teacher, and disaster preparedness school manager. The quantitative data were analyzed using the descriptive statistical technique. The qualitative data were used to support the quantitative data. The results of the study are as follows. 1) The level of preparedness of students of SMP Negeri 2 Pakem is high with a mean score of 141.93. The percentages of the student's preparedness to face the Mount Merapi eruption disaster are very high (34%) and high (66%). 2) The efforts made by the school to improve the preparedness of students of SMP Negeri 2 Pakem students include the provision of disaster socialization and simulation every year, the integration of disaster preparedness materials into the curriculum of learning, the school's provision of facilities related to the disaster preparedness school and an MoU between SMP Negeri 2 Pakem and SMP Negeri 2 Ngaglik as a buffer school during the Mount Merapi eruption disaster. 3) The school's constraints in improving preparedness are, among others, that not all materials can be integrated with the implementation of the disaster preparedness school, simulation and socialization conducted only once a year are considered not being maximal enough, and there is a student shift every year.